A novel ascosporogenous yeast species, Zygosaccharomyces siamensis, and the sugar tolerant yeasts associated with raw honey collected in Thailand - Sujinan Saksinchai (2018)
Diversity of yeasts in association with bees and their food sources has been explored during the last decade. In Thailand, there has been no study of yeast identification in honey and bees. Hence, a total of 186 yeast strains were isolated from 37 honey samples of 12 different bee species. On the basis of morphological and physiological characteristics, 55 representative strains were chosen and identified by sequence analysis of the 26S rDNA D1/D2 domain and the ITS region. The data were compared with the published sequences and the results showed the occurrence of 19 ascomycetous and 1 basidiomycetous yeast species. Six strains of the new species were isolated. Phylogenetic analysis of the 26S rDNA D1/D2 sequence revealed that they were conspecific and most closely related to Zygosaccharomyces mellis. Based on the ITS sequence, the new species was clustered with the type β and clearly distinguished from the type α. Sequence analysis of combined ITS-26S rDNA D1/D2 showed similar results. The occurrence of these two types, with a divergence of more than 1% in their sequences, and low DNA relatedness among them suggested that members of the type β can be regarded as separate species. An analysis of the morphological and physiological characteristics was performed. Ascospore formation was observed on acetate agar and Gorodkowa agar. The new Zygosaccharomyces species differed physiologically from Z. mellis in 4 assimilation tests. This data supports the hypothesis that the new species, Zygosaccharomyces siamensis, is a novel ascosporogenous yeast. The type strain is JCM 16825 T (=CBS 12273 T) and a description is given here. © Kevin D. Hyde 2011.